2021
DOI: 10.1016/j.neuron.2020.10.032
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of the Hypothalamo-Neurohypophysial System and Functional Dissection of Magnocellular Oxytocin Neurons in the Brain

Abstract: Highlights d A three-dimensional architecture of the HNS with high resolution was reconstructed d Magnocellular neuroendocrine cells collaterally projected to extrahypothalamic areas d Activation of Magno-OXT neurons promoted social behavior and peripheral OXT release d Inhibition of Magno-OXT neurons elicited opposite effects

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(57 citation statements)
references
References 75 publications
2
53
0
Order By: Relevance
“…In addition to the well-described somatodendritic release of OT, which takes place within the hypothalamic nuclei, the PVN and SON, specifically during lactation (Landgraf and Neumann, 2004 ; Ludwig and Leng, 2006 ; Tobin et al, 2014 ), OT neurons project distant axons throughout most of the forebrain and parts of the brain stem (Knobloch et al, 2012 ; Zhang et al, 2020 ), releasing a small number of large dense-core vesicles containing OT within a target region in non-synaptic fashion (Chini et al, 2017 ). The distribution of OT axonal terminals largely overlaps with OTR in target brain areas (Tribollet et al, 1988 , 1991 ; Campbell et al, 2009 ; Grinevich et al, 2016 ; Mitre et al, 2016 ).…”
Section: Brain-wide Ot Modulationmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the well-described somatodendritic release of OT, which takes place within the hypothalamic nuclei, the PVN and SON, specifically during lactation (Landgraf and Neumann, 2004 ; Ludwig and Leng, 2006 ; Tobin et al, 2014 ), OT neurons project distant axons throughout most of the forebrain and parts of the brain stem (Knobloch et al, 2012 ; Zhang et al, 2020 ), releasing a small number of large dense-core vesicles containing OT within a target region in non-synaptic fashion (Chini et al, 2017 ). The distribution of OT axonal terminals largely overlaps with OTR in target brain areas (Tribollet et al, 1988 , 1991 ; Campbell et al, 2009 ; Grinevich et al, 2016 ; Mitre et al, 2016 ).…”
Section: Brain-wide Ot Modulationmentioning
confidence: 99%
“…Although it is becoming clearer how OT may affect sensory systems, the mechanisms underlying targeted axonal release of OT in the socially relevant brain regions remain elusive. While an extensive series of tracing experiments were performed in the 1970s and 1980s (Sawchenko and Swanson, 1983 ), only a few recent studies have described the inputs and outputs of OT neurons with modern neuroanatomical techniques (Grinevich and Stoop, 2018 ; Son et al, 2020 ; Tang et al, 2020 ; Zhang et al, 2020 ). Thus, here we will first review outputs of OT neurons and their effects with an emphasis on cortical sensory regions.…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, oxytocin exerts distal effects within the brain via axonal projections originating from mostly parvocellular PVN neurons and reaching multiple brain areas that are involved in the control of eating behavior [ 11 , 25 ] ( Figure 1 ). Very recently, a subset of magnocellular neurons that also sends axonal projections within the brain has been discovered and is discussed subsequently [ 26 ]. Among the brain areas which the oxytocinergic neurons reach is the adjacent ARC [ 27 ], a major hub of appetite regulation which houses first-order anorexigenic neurons that express pro-opiomelanocortin (POMC) and cocaine- and amphetamine-regulated transcript to induce satiety, along with orexigenic neurons that signal hunger by releasing Neuropeptide Y (NPY) and Agouti Related Peptide (AgRP) [ 17 , 28 ].…”
Section: The Central Oxytocinergic System—a Framework To Understand the Role Of Oxytocin In The Coordination Of Energy Balancementioning
confidence: 99%
“…In contrast, centrally injected alpha-melanocyte stimulating hormone (alpha-MSH), which has a pivotal role in inducing satiety, acts on SON oxytocin receptors expressing alpha-MSH receptors to directly stimulate central oxytocin dendritic release while simultaneously suppressing electrical activity of oxytocin cells and thus the secretion of oxytocin into the systemic circulation [ 67 ]. Very recently, a meticulous description of oxytocin connectivity has been achieved in rodents using state-of-the-art engineered viral tracers [ 26 ]. This study showed that a subset of magnocellular oxytocin neurons collaterally and simultaneously projects to both the posterior pituitary and additional brain areas involved in reward and reinforcement-based learning behaviors (e.g., the amygdala, dorsal striatum, lateral septum, and NAc) [ 26 ] ( Figure 1 ).…”
Section: Observational Studies In Humans-relation Of Oxytocin To Food Intake Weight Status and Metabolismmentioning
confidence: 99%
See 1 more Smart Citation